2020
DOI: 10.3390/foods9020211
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Drying of Blueberries: Effects of Carbon Dioxide (CO2) Laser Perforation as Skin Pretreatment to Improve Mass Transfer, Primary Drying Time, and Quality

Abstract: Freeze-dried berry fruits are generally consumed as they are, whole and without peeling or cutting, as the conservation of their original shape and appearance is often desired for the final product. However, usually, berries are naturally wrapped by an outer skin that imparts a barrier to vapor flow during freeze-drying, causing berry busting. Photo-sequence, experimental, and theoretical methodologies were applied to evaluate the application of CO2 laser microperforations to blueberry skin. Under the same set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Munzenmayer et al (2020) reported reductions in the primary drying time of freeze‐dried blueberries when skin microperforations were made, which was in addition to significant quality improvements; the same was observed with tomato peeling performed by Silva et al (2020), and skin microperforations not only accelerated of the process but also decreased the energy requirements. Figueroa et al (2020) found that the application of pulsed vacuum impregnation and CO 2 laser microperforations accelerated the pork marination process with a maximum processing time reduction of 47%.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Munzenmayer et al (2020) reported reductions in the primary drying time of freeze‐dried blueberries when skin microperforations were made, which was in addition to significant quality improvements; the same was observed with tomato peeling performed by Silva et al (2020), and skin microperforations not only accelerated of the process but also decreased the energy requirements. Figueroa et al (2020) found that the application of pulsed vacuum impregnation and CO 2 laser microperforations accelerated the pork marination process with a maximum processing time reduction of 47%.…”
Section: Resultsmentioning
confidence: 74%
“…Formation of micropores in the sample favors the mass transfer process. This has been reported in salmon tissue brining (Olivares et al, 2021), pork marination (Figueroa, Ramírez, Nuñez, Jaques, & Simpson, 2020), tomato peeling with lye (Silva et al, 2020), fruit peeling (Panchev, Kirtchev, & Dimitrov, 2011), the freeze drying of blueberries (Fujimaru, Ling, & Morrissey, 2012; Munzenmayer et al, 2020), and dough browning (Blutinger et al, 2019). Independent of the product, microperforation had reported significant time reductions varying between 48 and 67% with respect to nonmicroperforated samples, depending on the matrix and mass transfer performed.…”
Section: Introductionmentioning
confidence: 80%
“…Such a phenomenon is possible under adequate temperature and pressure (below the triple point to enable the conversion of ice into vapour), when water molecules have enough energy to break free from the frozen material, but the conditions cannot support the formation of a liquid [5,6]. Vacuum FD process is commonly carried out at a low temperature (shelf temperature below 50 • C) [7] and low pressure (below the vapour pressure at the ice surface). Typically, the vacuum levels applied in the FD range between 7 and 70 Pa [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Concomitantly, the quality was also significantly improved, as the percentage of nonbusted blueberries at the end of the process increased from an average of 47% to 86%. It was demonstrated that CO 2 -laser microperforation has high potential as a skin pretreatment for the freeze-drying of blueberries [12].…”
Section: Introductionmentioning
confidence: 99%